2006
DOI: 10.1086/508293
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Monoclonal Antibody against West Nile Virus Envelope Protein Administered after Neuronal Infection Protects against Lethal Encephalitis in Hamsters

Abstract: Humans infected with West Nile virus (WNV) may clinically present with symptoms that are suggestive of neurological infection. Nearly all treatments of WNV disease have been effective in animal models only if administered before or soon after viral challenge. Here, we evaluated whether a potent neutralizing anti-WNV humanized monoclonal antibody (MAb), hE16, could improve the course of disease in a hamster model when administered after the virus had infected neurons in the brain. Five days after viral injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 38 publications
3
85
0
Order By: Relevance
“…Studies in murine models using low doses of IVIG preparations that contained high titres of WNV neutralizing antibodies confirmed robust protection from WNV encephalitis (Ben-Nathan et al, 2003. Passive transfer of WNV-specific monoclonal or murine polyclonal antibodies aborted or limited WNV infections in rodent models in a dose-, time-and complementdependent manner (Agrawal & Petersen, 2003;Mehlhop et al, 2005;Morrey et al, 2006). Our earlier investigation of the protective mechanisms of IVIG in a model of herpes simplex virus type 1 (HSV1) encephalitis demonstrated that IVIG's potent anti-inflammatory and immunomodulatory activities, rather than its neutralizing activity, were essential for protection.…”
Section: Introductionmentioning
confidence: 84%
“…Studies in murine models using low doses of IVIG preparations that contained high titres of WNV neutralizing antibodies confirmed robust protection from WNV encephalitis (Ben-Nathan et al, 2003. Passive transfer of WNV-specific monoclonal or murine polyclonal antibodies aborted or limited WNV infections in rodent models in a dose-, time-and complementdependent manner (Agrawal & Petersen, 2003;Mehlhop et al, 2005;Morrey et al, 2006). Our earlier investigation of the protective mechanisms of IVIG in a model of herpes simplex virus type 1 (HSV1) encephalitis demonstrated that IVIG's potent anti-inflammatory and immunomodulatory activities, rather than its neutralizing activity, were essential for protection.…”
Section: Introductionmentioning
confidence: 84%
“…Passive transfer of monoclonal or polyclonal antibodies protect mice and hamsters from lethal subcutaneous or intraperitoneal WNV challenge [5][6][7][8]10,11,15,40,56]. To address the relative potency of the WNV-specific antibody response generated by the vaccines, we passively transferred serum from immunized to younger naïve mice before lethal peripheral challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This mAb is highly inhibitory because it blocks viral fusion at concentrations that result in low occupancy of accessible sites on the virion (10,11). Hu-E16 has therapeutic activity in rodents even after WNV has entered the central nervous system (9,12), in part because it can directly disrupt virus transmission between neurons (13). Despite the promise that Hu-E16 and other mAbs have as prophylactics and therapeutics for WNV or other infectious diseases, their application may be limited by the high production costs and scalability associated with the mammalian-cell culture production system.…”
mentioning
confidence: 99%